Sistem Informasi Simpan Pinjam Pada Koperasi Guru Dan Karyawan “Dwija Bhakti” SMA Negeri 2 Mranggen Berbasis Multi User - Lutmawati Lutmawati; Kasih Purwantini; Arsito Ari Kuncoro; Iman Saufik Suasana; Febryantahanuji Febryantahanuji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Purpose of this study is to create a storage information system so that there is no wrong recording. Creating an automatic data search information system so that there is no need to search in a ledger, Creating an accurate information system in calculating savings, loans, installments and the distribution of the remaining operating results (SHU) automatically, Creating an information system that will make it easier to make the right reports, fast and accurate for cooperatives. The problem that arises in this cooperative is that the process of recording and searching for data on deposits, loans and installments is still manual in the form of a ledger. Another obstacle encountered is the calculation of deposits, loans, installments and SHU still using Microsoft Excel, which is still possible for errors in calculations. In addition, report generation also uses Microsoft Excel which requires data recording one by one which results in the presentation of the report taking a long time. The method used in this research is multi-user based using Visual Basic software, MySQL database and peer to peer network topology. The results of the analysis obtained from this study are the application of cooperative The savings and loan information systems that have been validated through several stages